ANALISIS PMK NO. 66 TAHUN 2023 DALAM KEBIJAKAN PEMBERIAN NATURA DAN CORPORATE SUSTAINABILITY - Edryanto Edryanto; Harti Budi Yanti (JURNAL LENTERA BISNIS, 2025)
Significant changes in Indonesia’s tax regulations following the COVID-19 pandemic were a response to the national economic instability, particularly in 2020, when economic growth, based on Gross Domestic Product at Constant Prices, and tax revenues experienced a notable decline. The objective of this study is to analyse the implementation of Minister of Finance Regulation (PMK) Number 66 of 2023 concerning the income tax treatment of benefits in kind and/or allowances, as well as its impact on non-salary compensation policies and corporate sustainability strategies in security service companies. This research focuses on PT.XYZ, a company that routinely provides benefits in kind to its employees. A descriptive qualitative method with an instrumental case study approach was employed. Data were collected through interviews, observations, and document analysis, using thematic analysis and source triangulation techniques. The findings indicate that the allowances of benefits in kind can enhance tax efficiency, although it presents certain challenges. Therefore, a well-developed adaptation strategy is necessary to prevent negative impacts on employee motivation and, indirectly, to contribute to the environmental sector. These three aspects, employee retention, tax efficiency, and environmental contribution are integral components of the 3P (People, Profit, Planet) framework in corporate sustainability